Effects of indoor environment on EEG and thermal comfort under the ceiling-fan-integrated air conditioning system - Li, Wenqiang; Peng, Pei; Wang, Tao; Gong, Guangcai (Building and environment, 2024)
This study investigated the correlations between the relative EEG power at different frequency bands under ceiling-fan-integrated air conditioning (CFIAC) systems. Twenty subjects participated in the experiments with the combinations of five air temperature levels (24, 25, 26, 27, and 28 °C) and six ceiling fan gears (Levels 1, 2, 3, 4, 5, and closed). The EEG signals and indoor environmental parameters (relative humidity, air velocity, and temperature) were recorded synchronously, and the thermal comfort online survey for each subject was obtained as well. The most comfortable combination was found when the air temperature was 27 °C and the fan speed was 0.3 m/s. When the air temperature was 25 °C, the relative EEG power in the different bands was least distinguishable, but when the temperature rose to 27 °C, it occurred an obvious change in different lobes. The δ, θ, β, and γ-bands significantly correlated with indoor setting temperature for the whole brain, but only the θ-band located at the occipital lobe significantly correlated with ceiling fan speed. The significance for the α-band with setting temperature and the β-band signal with air velocity varies with the subjects. Compared to the common air conditioning (CAC) system, CFIAC had a different effect on the relationship between relative EEG power and exposure environment. The airflow due to the ceiling fan may reverse this relationship between α-band, β-band, and IAT from positive (CFIAC system) to negative (CAC system). This study can contribute to developing wearable sensing data-driven thermal comfort evaluation models. •25 °C was the most less distinguishable temperature for relative EEG power of different bands.•27 °C was the up threshold cause the obvious change of the relative EEG power in different lobes.•Significance for α-band to air temperature and β-band to air velocity varies with subjects.•Just θ-band bands at the occipital lobe significantly correlated with ceiling fan speed.•Airflow reverse the relationship between α (β)-bands and indoor temperature.